#### Answer

$-47$

#### Work Step by Step

We start with the given expression: $3x-2y-4x-x+7y$
We plug in the given values for $x$ and $y$: $3(6)-2(-7)-4(6)-6+7(-7)$
Order of operations states that first, we perform operations inside grouping symbols, such as parentheses, brackets, and fraction bars. Then, we simplify powers. Then, we multiply and divide from left to right. Then, we add and subtract from left to right. We follow order of operations to simplify:
First, we multiply from left to right: $18−2(−7)−4(6)−6+7(−7) =18-(-14)−4(6)−6+7(−7)=18-(-14)-24-6+7(-7)=18−(−14)−24−6+(-49)$
We add and subtract from left to right: $32-24-6+(-49)=8-6+(-49)=2+(-49)=-47$